1996
DOI: 10.1017/s1041610296002505
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Depression Scale: A Review of Its Development and Utility

Abstract: ABSTRACT. This article reviews the significance of the Geriatric Depression Scale (GDS) to practitioners and researchers in clinical gerontology, more than 10 years after the scale was introduced to the scientific community. This report summarizes findings from the most relevant validation studies in which this selfreport for assessing depression in elderly people has been tested. Included is discussion of the use of the GDS with specific populations (elderly medical inpatients, nursing home residents, and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(202 citation statements)
references
References 32 publications
4
186
0
9
Order By: Relevance
“…The Gds15 had a wider rOC curve indicating a higher discriminative property, and a more convenient approach to the left upper quadrant of the graph than the BdI. Other practical advantages of the Gds15 would be that it is shorter, easier and quicker to fill out than the BdI, none of the 15 items being somatic, and is currently one of the most used depression self-reported scales in the old age 17 . Our findings for the BdI are closely similar to those obtained by Leentjens et al 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The Gds15 had a wider rOC curve indicating a higher discriminative property, and a more convenient approach to the left upper quadrant of the graph than the BdI. Other practical advantages of the Gds15 would be that it is shorter, easier and quicker to fill out than the BdI, none of the 15 items being somatic, and is currently one of the most used depression self-reported scales in the old age 17 . Our findings for the BdI are closely similar to those obtained by Leentjens et al 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the most used screening instruments for depressive symptoms among elderly people. Several studies have shown that it provides valid and reliable measurements [10][11][12] . The original scale of 30 items was described in English by Yesavage et al 13 and was developed especially for the screening of mood disorders among elderly individuals, with questions that avoid the sphere of somatic complaints.…”
Section: Methodsmentioning
confidence: 99%
“…Although it performs well in patients with mild to moderate cognitive impairment, [152][153][154] the data on its validity in moderate to severely cognitively impaired patients are conflicting. 153,[155][156][157][158] The GDS is in the public domain (see, for example, Table 3) and has been translated in many European and Asian languages.…”
Section: Geriatric Depression Scale (Gds) Depression In Non-pd Patientsmentioning
confidence: 99%